PENGARUH GREEN MARKETING TERHADAP PENGAMBILAN KEPUTUSAN (Studi Empiris pada Greenhost Boutique Hotel Yogyakarta) - Deasy Lestary Kusnandar (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2016)
This study aims to determine the effect of green marketing on purchasing decisions with gender as a moderating variable. The location of this research is in Greenhost Boutique hotel located in Jl. Jl. Guerilla No. 629 Yogyakarta Prawirotaman II Brontokusuman This research is a quantitative research using surveys given to hotel guests. Then, the object of this research is a green product, green price, green place, green promotion and purchasing decisions. Determination of the number of samples in this study was 120 respondents to the sampling method used is to use random sampling. Measurement tool in this study using a 1-7 scale interval. Respondents gave answers on the answer ranges from strongly disagree to strongly agree. Then, the analysis is the analysis of Structural Equation Modeling (SEM). This analysis is aided by using a computer program AMOS 21. SEM analysis of the results of model-based development known theory in this study were 5 variables and 20 indicators. Path diagram drafting and preparation of structural and measurement equations are derived from the development of three models of research substructure. Input matrix used is covariant and the estimation technique used is the Maximum Likelihood (ML) Estimation, which has been available in the computer program AMOS 21. At this stage of Confirmatory Factor Analysis (CFA) no indicator is omitted, namely X16. Then, the construct validity test consisting of construct reliability, variance extracted, convergent validity, and discriminant validity has been fully met. On the assumption that SEM consists of evaluating the normality of the data, outliers, and multicolinierity & singularity also has met the required criteria. From 8 index criteria suitability model (goodness of fit test) were used as reference in this study, the ChiSquare, Probability, CMIN / DF, GFI, AGFI, TLI, CFI and RMSEA, there are eight criteria were categorized as good and the remaining two criteria categorized as marginal. Based on the results of hypothesis testing are known: (1) Green Product influence on purchasing decisions, (2) Green Price influence on purchasing decisions, (3) Green Place influence on purchasing decisions, (4) Green Promotion influence on purchasing decisions